ANALISA KEKERASAN PADA TARIKAN 2%, 4% DAN 8% BAJA BASE DAN BAJA Cu UNTUK MENDAPATKAN KEKERASAN PADA α dan α’ - Nofriady Handra (Jurnal Teknik Mesin (JTM), 2012)
This study will discuss change in tensile behavior as a function of vol.% of a’ in copper free and copper bearing dual phase steel. Microstructures of the steels after solution treatment and annealing at intercritical region are lath martensite and (a+a’) dual structures, respectively. The temperatures for annealing were determined using JMatPro 4.1. Specimens were austenised at 1000?C for 30 sec and followed by water quenching. Then, each type of specimens were heat treated at specific temperatures in order to obtain 20% and 80% of martensite. Beside that, for get hardness values each samples, the samples strain at 2%, 4% and 8% tensile test for base steel and Cu steel. Changes of hardness of annealed samples almost the same in both steels. On the other hand, it is found that addition of copper can improve tensile strength, total elongation and strength-ductility balance of the DP steel although no significant effect on yield stress and uniform elongation. Therefore, it can be concluded that the copper bearing DP steel has more excellent tensile properties than the copper free DP steel.